CFD Analysis on Aerodynamic Coefficients of Flying Saucer - Ruseno, N (International Journal of Aviation Science and Engineering - AVIA, 2021)
With the growing of Unmanned Aerial Vehicle (UAV) usage, many new types of UAV are introduced. Flying Saucer is a new type of UAV which is not yet famous in the market. The aim of this study is to analysis the aerodynamic coefficients of a Flying Saucer. The research question arise is What the optimum angle of attack for Flying Saucer flight is. The study is conducted in Computational Fluid Dynamics (CFD) using COMSOL Multiphysics with Laminar Flow physics for several angles of attack. The analysis considers Lift and Drag coefficient in the form of ???????? and ???????? to angle of attack (α) plot, ratio of ????????/???????? to angle of attack (α) plot and drag polar plot. We conclude that a symmetric Flying Sauce has aerodynamic characteristic with the optimum operational angle of attack in the range of 8 to 16 deg. The ???????? and ???????? has a quadratic relationship with large ????????0 due to the geometric of Flying Saucer. It recommends that further study should explore in the area of zero and maximum angle of attack (α) and validation in wind tunnel experiment.